Endothelin type A receptor blockade increases renoprotection in congestive heart failure combined with chronic kidney disease: Studies in 5/6 nephrectomized rats with aorto-caval fistula - Kala, Petr; Vaňourková, Zdenka; Škaroupková, Petra; Kompanowska-Jezierska, Elżbieta; Sadowski, Janusz; Walkowska, Agnieszka; Veselka, Josef; Táborský, Miloš; Maxová, Hana; Vaněčková, Ivana; Červenka, Luděk (Biomedicine & pharmacotherapy, 2023)
BACKGROUND: Association of congestive heart failure (CHF) and chronic kidney disease (CKD) worsens the patient's prognosis and results in poor survival rate. The aim of this study was to examine if addition of endothelin type A (ETA) receptor antagonist to the angiotensin-converting enzyme inhibitor (ACEi) will bring additional beneficial effects in experimental rats. METHODS: CKD was induced by 5/6 renal mass reduction (5/6 NX) and CHF was elicited by volume overload achieved by creation of aorto-caval fistula (ACF). The follow-up was 24 weeks after the first intervention (5/6 NX). The treatment regimens were initiated 6 weeks after 5/6 NX and 2 weeks after ACF creation. RESULTS: The final survival in untreated group was 15%. The treatment with ETA receptor antagonist alone or ACEi alone and the combined treatment improved the survival rate to 64%, 71% and 75%, respectively, however, the difference between the combination and either single treatment regimen was not significant. The combined treatment exerted best renoprotection, causing additional reduction in albuminuria and reducing renal glomerular and tubulointerstitial injury as compared with ACE inhibition alone. CONCLUSIONS: Our results show that treatment with ETA receptor antagonist attenuates the CKD- and CHF-related mortality, and addition of ETA receptor antagonist to the standard blockade of RAS by ACEi exhibits additional renoprotective actions.
Keywords: Rats; inhibitory ACE; Angiotensin-Converting Enzyme Inhibitors; antagonisté endotelinového receptoru A; Renal Insufficiency, Chronic; chronická renální insuficience; píštěle; Congestive heart failure; Endothelin A Receptor Antagonists; renin-angiotensin systém; Endothelin-1; endotelin-1; krysa rodu Rattus; Rats, Transgenic; Chronic kidney disease; Aorto-caval fistula; zvířata; Fistula; Endothelin receptor type A; ledviny; Renin-Angiotensin System; srdeční selhání; 5/6 nephrectomy; Endothelin system; receptor endotelinu A; potkani transgenní; Kidney; Receptor, Endothelin A; Heart Failure; Animals